New Global Perspectives on Industrial Engineering and Management : International Joint Conference ICIEOM-ADINGOR-IISE-AIM-ASEM /: International Joint Conference ICIEOM-ADINGOR-IISE-AIM-ASEM. (2018) - Unknown
No abstract available